Spatial Analysis of Physical Parameters Influencing Water Quality: A Case Study in Seloromo Reservoir, Central Java, Indonesia - Rofiana Budi Ayumi Sita Dewi (BRIN Publishing, 2025)
Reservoirs are vital water resources that have an essential role from the perspective of living things. Utilization of reservoirs by humans frequently causes problems in the reservoir ecosystem, such as water pollution. Seloromo Reservoir was the second reservoir built to support various activities such as agriculture, fisheries, and tourism. Complex activities can influence the quality of reservoir water because sources of pollution are absorbed and flow into the water body. For this reason, monitoring is essential to determine factors that affect water quality of the reservoir. The aim of this research is to analyze the water quality of Seloromo Reservoir by testing physical parameters such as water temperature, degree of acidity (pH), Electrical Conductivity (EC), Total Dissolved Solid (TDS). In order to show the spatial distribution of each physical characteristic, grab samples were collected and measured in real time using a water checker. The results will be shown on a map. Spatial distribution maps were created by using the Inverse Distance Weighted (IDW) method which provides the simplest formulation and accurate results. Results show that human activities such as agriculture, livestock, and tourism around the reservoir and inputs from the river inlet indicate the condition of water quality in Seloromo Reservoir. Spatial distribution maps of physical parameters show that the northern area is more affected than the southern area of the reservoir. Local communities have an important role in conserving the water resources in this reservoir. Consequently, the research can contribute new knowledge about the condition of the reservoir and provide additional reference in establishing policies.